2009
DOI: 10.1038/ejcn.2009.139
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution and noncommunicable diseases in populations: overview of the 2008 WHO Expert Consultation on Waist Circumference and Waist–Hip Ratio

Abstract: A World Health Organization (WHO) Expert Consultation on Waist Circumference (WC) and Waist-Hip Ratio (WHR) was convened in Geneva from 8 to 11 December 2008 to consider approaches to developing international guidelines for indices and action levels in order to characterize health risks associated with these measures of body fat distribution-alternative or complementary to the existing WHO guidelines for assessments of generalized obesity on the basis of body mass index. Six background papers prepared for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
272
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(285 citation statements)
references
References 8 publications
7
272
1
5
Order By: Relevance
“…More recently, however, measures of body fat distribution, especially abdominal fatness, as reflected by waist circumference or waist-to-hip ratio (WHR), have been suggested as a better indicator of the adverse metabolic effects of obesity (Snijder et al, 2006). A wide range of disease outcomes, especially chronic noncommunicable diseases have been examined in relation to obesity using either BMI or WHR in numerous studies (Pischon et al, 2006;Vazquez et al, 2007;Huxley et al, 2010) and the World Health Organization (WHO) has recently convened a consultation to discuss cut-points for waist circumference and WHR (Nishida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, however, measures of body fat distribution, especially abdominal fatness, as reflected by waist circumference or waist-to-hip ratio (WHR), have been suggested as a better indicator of the adverse metabolic effects of obesity (Snijder et al, 2006). A wide range of disease outcomes, especially chronic noncommunicable diseases have been examined in relation to obesity using either BMI or WHR in numerous studies (Pischon et al, 2006;Vazquez et al, 2007;Huxley et al, 2010) and the World Health Organization (WHO) has recently convened a consultation to discuss cut-points for waist circumference and WHR (Nishida et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, obesity with central visceral fat accumulation (VAT) has been associated with a higher risk of the metabolic syndrome (MetS) and may enhance the endocrine avtivity of the tissue (Nishida et al, 2010). In fact, the European Prospective Investigation into Cancer and Nutrition (EPIC) reported that visceral obesity (VAT), rather than the total amount of fat, is linked to a strong risk factor for CRC regardless of the gender, age, or ethnic background (Pischon et al, 2006).…”
Section: Obesity Markers and Relation To Crc Developmentmentioning
confidence: 99%
“…WC equal to or higher than 88 cm (in women) or 94 cm (in men) and WHR above 0.90 for males and 0.85 for females are cut off points associated with a high metabolic risk (Nishida et al, 2010). A recent meta-analysis of 21 studies has revealed that a 10-cm increase in WC is related to an increased risk of colorectal adenoma (CRA), regardless of the geographic region, gender, and confounders: alcohol use, smoking status, and family history of colorectal cancer (Hong et al, 2012;Kaneko et al, 2014).…”
Section: Obesity Markers and Relation To Crc Developmentmentioning
confidence: 99%
“…Se define como sobrepeso un . El Índice Cintura-Cadera (ICC) es un coeficiente que relaciona la disposición del tejido adiposo de un individuo, siendo un cociente entre la circunferencia de la cadera en centímetros y la circunferencia de la cintura en centímetros y definiendo como obesidad, un ICC mayor o igual a 0,9 para los hombres y un ICC mayor o igual a 0,85 para las mujeres 2,3 . La prevalencia de sobrepeso y obesidad está aumentando de forma alarmante, tanto en países desarrollados como en vía de desarrollo 4,5 , relacionándose con la aparición de enfermedades cardíacas, metabólicas, renales, desórdenes del sueño, cáncer y problemas mentales [6][7][8][9][10][11][12] .…”
Section: Introductionunclassified